Electrochemically Active Biofilms as an Indicator of Soil Health. Issue 8 (26th August 2021) - Mohamed, Abdelrhman; Sanchez, Eduardo; Sanchez, Natalie; Friesen, Maren L.; Beyenal, Haluk
Abstract : Soil health is a complex phenomenon that reflects the ability of soil to support both plant growth and other ecosystem functions. To our knowledge, research on extracellular electron transfer processes in soil environments is limited and could provide novel knowledge and new ways of monitoring soil health. Electrochemical activities in the soil can be studied by inserting inert electrodes. Once the electrode is polarized to a favorable potential, nearby microorganisms attach to the electrodes and grow as biofilms. Biofilms are a major part of the soil and play critical roles in microbial activity and community dynamics. Our work aims to investigate the electrochemical behavior of healthy and unhealthy soils using chronoamperometry and cyclic voltammetry. We developed a bioelectrochemical soil reactor for electrochemical measurements using healthy and unhealthy soils taken from the Cook Agronomy Farm Long-Term Agroecological Research site; the soils showed similar physical and chemical characteristics, but there was higher plant growth where the healthy soil was taken. Using carbon cloth electrodes installed in these soil reactors, we explored the electrochemical signals in these two soils. First, we measured redox variations by depth and found that reducing conditions were prevalent in healthy soils. Current measurements showed distinct differences between healthy and unhealthy soils. Scanning electron microscopy images showed the presence of microbes attached to the electrode for healthy soil but not for unhealthy soil. Glucose addition stimulated current in both soil types and caused differences in cyclic voltammograms between the two soil types to converge. Our work demonstrates that we can use current as a proxy for microbial metabolic activity to distinguish healthy and unhealthy soil.